Understanding the decision-making structures, roles and actions of village-level water committees in Fiji. Issue 3 (4th May 2022) - Nelson, Sarah; Abimbola, Seye; Mangubhai, Sangeeta; Jenkins, Aaron; Jupiter, Stacy; Naivalu, Kelera; Naivalulevu, Vilisi; Negin, Joel
ABSTRACT: As part of a community-based project on water-related disease in Fiji, we conducted a qualitative study to assess the decision-making structures, roles and actions of village-level water committees. Village water committees played a role in the management, operation and maintenance of water and sanitation infrastructure. Reactive and proactive management approaches were both present. The water committees had clear processes in place for decision-making and membership and were influenced by social and cultural norms. Men dominated water committee membership, roles and decision-making. Knowledge about governance structures and processes can be used to strengthen systems for water committees to effectively manage water access and security.